PURSE SEINE FISHERY FOR OIL SARDINE OFF COCHIN DURING THE YEARS 1980-’85 - Balan, V; Nizar, M Abdul (Indian Journal of Fisheries, 2011)
Observations on the purse-seine fishery for oil sardine at Cochin indicated that the fishery fluctuated widely during 1980-’85. The best catch was in 1984 (17,665.90 t) and the poorest in 1985 (5,470.27 t). The highest monthly catch rate (1,181.0 kg) was in December, 1984 while the lowest (295.4 kg) in November, 1982. Range of total instantaneous mortality ’Z’ was from 1.59 to 2.88, the average being 2.15. The natural mortality ’M’ worked out to 0.75. The instantaneous fishing mortality ’F’ has been estimated to be 1.4. The annual rate of exploitation ’a* has been estimated to be 0.5743. Average annual purseseine catch (A1) of oil sardine during these six years was 10,3361. The standing stock at Cochin for 1980- ’85 has been calculated at 7,383 t. The average annual stock of oil sardine at Cochin has been estimated at 17,998 t. Average annual catch of oil sardine in Kerala during the 6-year period was 1,23,519 t; the standing stock has been estimated at 88,228 t and the average annual stock has been calculated as 2,15,077 t. For Cochin, the MSY has been estimated to be about 12,500 t; and for Kerala the value has worked out to about 1,50,0001. The Beverton and Holt yield per recruit analysis revealed that any further increase in the rate of exploitation (i.e. 0.65) by purse seiners would not result in significant increase in the yield; but by increasing the length at first capture from 125 to 145 mm, might yield higher catches. The 15-40 m depth area was found to be the most productive. Preponderance of 0-year recruits was observed during 1980-’85 (except in 1983) whereas the 1 + year group had only a secondary dominance. The study revealed that the success of the sardine fishery in any year was mainly dependent on the abundance of the 0-year recruits. Though a small-scale spawning was noticeable by the end of May, the peak spawning was during June to August off Cochin. Application of Chi-square test on sex composition indicated predominance of females during 1980-’84 in purse-seine catches.